A Study of Influence of Corporate Social Responsibility (Csr) and Advertisements with a Social Dimension of Firms in Consumer Purchase Intent in Malaysia - Syed Tahir, Sharifah Nur Adibah (2006)
Most of the corporate social responsibility (CSR) studies conducted so far have been in the context of developed countries. Very few studies are available on the CSR practices in Malaysia which are in the context of company perspective. Fewer studies were found about CSR from the consumers’ point of view conducted in Malaysia. No study was found about CSR and advertising from the consumers’ point of view conducted in Malaysia. Research in this area is important as it will provide greater insight on the extent of CSR among Malaysians. It will also show the attitudes of consumers towards CSR in a developing country like Malaysia. Further, this research may provide implications to businesses in Malaysia, a developing country, whose consumers may have different meanings of CSR compared to consumers of the developed countries- specially the Western countries. Corporations are turning to all forms of corporate societal marketing programs to help build, and in some cases, repair their brand images. These marketing programs have both potential dangers and rewards for the firms. Today advertising penetrates into the life of every person. This paper investigates how consumers evaluate advertisements with a social dimension in five different industries. This research attempts to examine Malaysian consumers’ responses to newspaper, magazine and television advertising for aspects relating to the communication process. This research will also show whether CSR content in advertising is a sufficient attempt to create a purchase intention among consumers.